ASPEK SOSIAL EKONOMI TANAMAN AREN - Subandi Antaatmadja (Jurnal Penelitian Hasil Hutan, 1989)
Aren  tree is one  of  the  members   of palm  family.   The  distribution   extends   in all Indonesian  area.  The main produc- tion  of  aren juice   for  material  of  sugar,  are aren fruits  for  food,  fiber  mode  for plait  material  handcraft,   and  numeroua  utilization.  The study   of  aren  trees in Cianjur  Concludes  :1.The  aren  trees  are found   in all districts.                                                                      2.The  study   in a sub  district  of  Cianjur  reveals  that  :a.Cibinong  is one  of  the  biggest  sub  district   where  aren  stands  were  found.b.Total production  of  brown  sugar in  1986  in this  sub  district  was  549  tons  with  831   farmers.   Average  sugar pro-  duction   ammounts    to  0.661    ton/farmer.c.Average  input   in  aren  busines  is  2.12   hours/day/house   hold.d.The  small  holder  of  the  aren starch  production  having  capacity   of  72  tons/year   requires  total  investment  of  Rp  1,505,000.-    and production   cost:   Rp  11,140,000.-/year    giving  the  financial  earning  of Rp  7,500,000.-